PENGARUH KONSENTRASI EKSTRAK DAUN KELOR (Moringa oleifera L.) TERHADAP MORTALITAS Sitophilus zeamais Motsch. : - - Harsanti, Restiani Sih; Yasi, Ratna Mustika (Program Studi Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2024)
Corn is the strategic commodity in Indonesia. The quality of many domestic corn does not meet feed factory standards. High yield losses icause of damage due to warehouse pests. Sitophilus zeamais Motsch or powder beetle is a warehouse pest that causes seeds to become hollow, break quickly and disintegrate into flour. Sitophilus zeamais Motsch pest control still relies on synthetic pesticides. The use of synthetic pesticides will cause various negative impacts such as pest resistance, residue, resurgencies, high costs and environmental pollution. One alternative for controlling Sitophilus zeamais Motsch is to use natural ingredients, namely Moringa. Moringa leaves contain phenol, hydroquinone, flavonoids, steroids, triterpenoids, tannins, alkaloids and saponins. The experiment began by drying 10 grams of Moringa leaves. then puree using a blender and continue with maceration. 200, 400, 600, 800, and 1000 mg of Moringa leaf powder were dissolved in 1 L of distilled water solution and left for 24 hours. After 24 hours, the solution was filtered 3 times so that all the substances contained in the Moringa leaves are extracted. The insecticide was tested by observing the number of S. zeamais pests that died when given Moringa leaf extract. The mortality data that was obtained was analyzed using ANOVA, if there was a real effect then continued using the 5% DMRT test. Determination of LC50 using a probit test. Moringa extract can function as a vegetable insecticide for S.zeamais. The higher concentration of Moringa leaf extract can increase the mortality of S.zeamais